Vertical Farming of Horticulture Crops: A Recent Trend - Pallvi Verma,; Manish Bakshi,; Lakshya, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Vertical farming now a day is gaining status as complementary to traditional farming practices, allowing for more sustainable food production for the world's growing population. While early studies on vertical farming systems focused primarily on the advancement of technology through innovative designs, hydroponic cultivation automation monitoring, and the use of advanced LED lighting systems, more recent studies have focused on the resilience and circularity of vertical farming. Over the last few decades, there have been elevated concerns about ethical cultivation practices and environmental issues, reliance on non renewable resources, commitment to biodiversity conservation, ration scarcity, and its leverage to hunger. Environmental issues, such as economic justice issues, biodiversity commitments, and a focus on food security issues, have gained traction in social work. Vertical farming is one of the solutions to many problems including food and nutritional security, environment safety, resource utilization, land fragmentation, climate resilience agriculture, etc.